STRATEGI KOMUNIKASI PERSUASIF GURU TAHFIDZ DALAM MENINGKATKAN MINAT MENGHAFAL AL-QUR’AN SISWA KELAS 3 DI MAN3 TANAH DATAR - Ilyana, Nurul Hasya; Nupiah, Ali (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research is motivated by the issue of communication in the tahfidz (Qur'an memorization) subject at MAN 3 Tanah Datar, specifically in 3rd-grade classes, where this issue affects the lack of interest in the Qur'an memorization process among students. Issues such as lack of focus and decreasing memorization abilities have been observed. Based on these problems, the researcher aims to conduct a more in-depth study regarding the communication process in tahfidz learning through psychodynamic persuasive communication strategies and sociocultural persuasive communication strategies at MAN 3 Tanah Datar. The research design used in this study is qualitative descriptive. This research provides an overview and analyzes data based on the results of field observations. The research instrument used is a written guide for interviews, observations, or a questionnaire, which is prepared to gather information from the subjects of the study, who are the tahfidz teachers at MAN 3 Tanah Datar. The data analysis technique employed in this study consists of data reduction, data presentation, and drawing conclusions. Based on the research findings regarding the persuasive communication strategy employed by tahfidz teachers to enhance students' Quranic memorization abilities at MAN 3 Tanah Datar, it is evident that various approaches are utilized by teachers to elevate students' interest in memorizing the Quran. These approaches include emotional, psychological, and structural dimensions. Through these approaches, there exists substantial potential to ignite students' enthusiasm and enhance their motivation for Quranic memorization.